Angiographic profile of NSTEMI patients with or without metabolic syndrome (Bangladesh Journal of Medical Science, 2016)
Background: Metabolic syndrome (MS) constitutes the clustering of clinical and biochemical risk factors, which are associated with increased risk of cardiovascular events. Non ST elevation myocardial infarction (NSTEMI) accounts for the important part of acute coronary syndrome (ACS) with considerable morbidity and mortality. The aim of this study was to investigate the association of MS with angiographic severity of coronary artery disease (CAD) in patients with NSTEMI.Methods: This study included 192 prospectively enrolled NSTEMI patients. The patients underwent coronary angiography (CAG). CAG were evaluated via Sullivans method.Results: Statistically significant difference in vessel score observed, such that higher triple vessel disease (TVD) in MS patients (42.7% vs. 15.6%, p